1990
DOI: 10.1055/s-2008-1053595
|View full text |Cite
|
Sign up to set email alerts
|

Rekonstruieren statt resezieren: Laminotomie und Laminoplastik

Abstract: Spinal instability and deformity have to be kept in mind when performing laminectomies. The procedure described (laminotomy) results in a stable bony reconstruction of the spinal canal, which in addition may be enlarged (laminoplasty): Laminotomy is performed by means of an oscillating saw just medial of the pedicles, preserving the yellow and interspinous ligaments. The laminotomy specimen is removed en bloc. It can be refixed by means of vitallium plates, bridging the corresponding laminae and pedicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Furthermore, our findings suggest that the presence of pain distributed along with a dermatome, radicular pain, hypoesthesia, paresthesia, dysesthesia, urinary and fecal incontinence, as well as gait disorders in a child otherwise healthy, should suggest the presence of a spinal cord tumor. Regarding surgical management of these lesions, we found that laminotomy by posterior approach is a safe and not deforming procedure, as previously reported 13,14 . Interestingly, we also observed that laminectomy caused kyphosis in only 1 of 17 patients subjected to such procedure at least until the last known follow-up, which represents a lower frequency than reported by other researchers who described that two-thirds of the subjects undergoing laminectomy developed deformity of the spine 31 , especially when laxity of supporting tissues was induced by the adjuvant oncological treatment 32 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, our findings suggest that the presence of pain distributed along with a dermatome, radicular pain, hypoesthesia, paresthesia, dysesthesia, urinary and fecal incontinence, as well as gait disorders in a child otherwise healthy, should suggest the presence of a spinal cord tumor. Regarding surgical management of these lesions, we found that laminotomy by posterior approach is a safe and not deforming procedure, as previously reported 13,14 . Interestingly, we also observed that laminectomy caused kyphosis in only 1 of 17 patients subjected to such procedure at least until the last known follow-up, which represents a lower frequency than reported by other researchers who described that two-thirds of the subjects undergoing laminectomy developed deformity of the spine 31 , especially when laxity of supporting tissues was induced by the adjuvant oncological treatment 32 .…”
Section: Discussionsupporting
confidence: 83%
“…1C). From these, 17 were laminotomies followed by laminoplasty as previously described 13,14 . Furthermore, 17 laminectomies (34%) and 5 hemi-laminectomies (10%) were performed (Fig.…”
Section: Surgical Managementmentioning
confidence: 99%